Transcription factor Six2 induces a stem cell‐like phenotype in renal cell carcinoma cells - Na Cheng; Hongjuan Li; Yan Han; Shuzhen Sun (FEBS Open Bio, 2019)
Renal cell carcinoma (RCC) accounts for 2–3% of adult malignant tumors, and the incidence of RCC worldwide has increased by about 2% over the past two decades. The homeobox protein Six2 has been shown to promote the stemness of breast cancer cells and play a role in kidney development, but its involvement in RCC progression has not previously been investigated. Here, we found that six2 expression was significantly increased in RCC tissues and negatively correlated with the overall survival of patients with RCC. In addition, six2 expression exhibited a remarkably higher level relative to that in normal renal cells. Functional experiments showed that six2 knockdown attenuated the stemness of RCC cells, which was evident by decreased spheroid formation ability and stemness marker (sox2 and nanog) expression. Mechanistic studies indicated that Six2 directly bound to the enhancer of sox2, promoting sox2 expression and downstream effector expression of nanog. Furthermore, overexpression of sox2 rescued the inhibitory effects of six2 on the stemness of RCC cells. Notably, six2 expression is positively correlated with sox2 and nanog expression in RCC tissues. Collectively, our results point toward a six2/sox2 axis responsible for RCC cell stemness.